Cell wall integrity, genotoxic injury and PCD dynamics in alfalfa saponin-treated white poplar cells highlight a complex link between molecule structure and activity. (March 2015) - Paparella, Stefania; Tava, Aldo; Avato, Pinarosa; Biazzi, Elisa; Macovei, Anca; Biggiogera, Marco; Carbonera, Daniela; Balestrazzi, Alma
Abstract : Graphical abstract: Biological effects of Medicago sativa purified saponins were tested on proliferating white poplar cell suspension cultures. TEM analysis along with cytotoxicity and genotoxicity assays were performed. Highlights: Cytotoxicity assessment of Medicago sativa purified saponins on white poplar cells. Saponins exert cell wall perturbation and plasma membrane disruption. Reported activation of ROS- and NO-mediated signaling pathways. Accumulation of SSBs and DSBs shows different profiles based on saponin structure. A working hypothesis of the molecular events triggered by saponins is proposed. Abstract: In the present work, eleven saponins and three sapogenins purified from Medicago sativa were tested for their cytotoxicity against highly proliferating white poplar ( Populus alba L.) cell suspension cultures. After preliminary screening, four saponins with different structural features in terms of aglycone moieties and sugar chains (saponin3, a bidesmoside of hederagenin; saponins4 and5, monodesmoside and bidesmoside of medicagenic acid respectively, and saponin10, a bidesmoside of zanhic acid) and different cytotoxicity were selected and used for further investigation on their structure–activity relationship. Transmission Electron Microscopy (TEM) analyses provided for the first time evidence of the effects exerted by saponins on plant cell wall integrity. Exposure to saponin3 and saponin10 resulted into disorganization of the outer wall layer and the effect was even more pronounced in white poplar cells treated with the two medicagenic acid derivatives, saponins4 and5 . Oxidative burst and nitric oxide accumulation were common hallmarks of the response of white poplar cells to saponins. When DNA damage accumulation and DNA repair profiles were evaluated by Single Cell Gel Electrophoresis, induction of single and double strand breaks followed by effective repair was observed within 24 h. The reported data are discussed in view of the current issues dealing with saponin structure–activity relationship.